THYROID AUTOIMMUNITY FOLLOWING ALEMTUZUMAB TREATMENT FOR MS. Issue 12 (15th November 2016) - Healy, Sarah; Nasser, Taha; Willis, Mark; Muller, Ilaria; Harding, Katharine; Pickersgill, Trevor; Wardle, Mark; Dayan, Colin; Robertson, Neil
Abstract : Introduction: Alemtuzumab is effective in active relapsing MS, although autoimmune disease (AID) is a recognised adverse event. We present long-term outcomes of the most common AID (thyroid), in order to inform pre-treatment counselling and subsequent disease management. Methods: 87 patients treated with alemtuzumab were followed within an active surveillance program and detailed data collected prospectively. Standard clinical indices, thyroid diagnosis, thyroid function tests, thyroid autoantibodies and treatment were recorded. Results: Mean follow-up was 7.4 years. 31 (36%, 24F:7M) developed thyroid AID. Mean interval from first treatment was 3.0 years (range 0.8–8.7); peak incidence in years 2–3. 12 (38.7%) patients developed hyperthyroidism, 8 (25.8%) subclinical hyperthyroidism, 8 (25.8%) hypothyroidism and 3 (9.7%) subclinical hypothyroidism. In 23 (74%) patients TPO antibodies were present during the disease course. Of 11 patients with hypothyroidism, 6 (55%) were TRAb positive. All patients received appropriate initial treatment for thyroid dysfunction. Three (9.7%) required propylthiouracil and 5 (16%) radioiodine. Two patients (6%) underwent thyroidectomy. No patients developed thyroid carcinoma. Discussion: Thyroid AID following alemtuzumab is a unique model of human autoimmunity and exhibits a variable presentation. When identified early and managed with specialist support it responds to standard treatments. AID can occur outside the recommended 4-year monitoring window and neurologists should remain vigilant for symptoms and have protocols for management.